A Liquid Gripper Based on Phase Transitional Metallic Ferrofluid. (19th May 2021) - Wang, Hongzhang; Chen, Sen; Li, Haowei; Chen, Xianzhe; Cheng, Jiashu; Shao, Yunlin; Zhang, Chenglin; Zhang, Jie; Fan, Linlin; Chang, Hao; Guo, Rui; Wang, Xuelin; et al.
Abstract: Magnetic fields enable dexterous, precise, and real‐time control of ferromagnetic materials. However, most materials, including glasses, organics, and metals, are nonmagnetic and often do not respond to a magnetic field. Here, a transitional ferrofluid (TF) made by embedding magnetic iron particles into pure gallium through the treatment of highly concentrated HCl solutions, as well as its switchable interlocking force to objects during the phase change, is introduced to achieve magnetic manipulation of non‐magnetic objects. A gripper made by liquid TF enables intimate contact with arbitrarily shaped objects and then generates a strong interlocking force of as high as 1168 N (using only 10 g TF) upon solidification at room temperature, which can be reversibly eliminated ( F < 0.01 N) through melting. Owing to electrical conductivity and magnetism, a solid TF can be melted through electromagnetic induction heating. By coupling the switchable physical force during the phase transition and magnetism of TF, embedded non‐magnetic objects can be manipulated using an applied magnetic field and become impervious to magnetic stimuli again after heating and releasing the TF. This study is expected to inspire numerous potential applications in the reversible magnetic actuation of soft robotics, remote operation systems, drug delivery, and liquid grippers. Abstract : A liquid gripper made of a gallium‐based transitional ferrofluid (TF) enables intimate contact with arbitrarily shaped objects and then generates a strong interlocking force upon solidification at room temperature, which can be reversibly eliminated by moderate heating. By coupling switchable physical force during the phase transition and magnetism of TF, embedded non‐magnetic objects can be manipulated using an applied magnetic field.